Emergency, Values and Evidence - Allen Alvarez; Espen Stabell; May Thorseth (Etikk i Praksis: Nordic Journal of Applied Ethics, 2020)
This open issue of the Nordic Journal of Applied Ethics consists of four papers that discuss the topics covering vaccination, sustainability, development ethics research and family ethics. It also includes a book review.